3D Blender and 3D Unity: Key Steps in Game Development and Modeling - Chorshanbieva Sarvinoz Berdimurod Kizi (Scientific Trends, 2025)
This article explores the interconnection between Blender and Unity software, detailing the processes of 3D modeling, animation, physics effects in games, interactive element creation, and monetization strategies. The paper discusses how high-quality 3D models can be designed in Blender and integrated into Unity for game development.
Keywords: Blender, Unity, 3D modeling, game development, animation, physics simulation, monetization.